CD5 positive diffuse large B cell lymphoma: case report and literature review - Beltrán Gárate , Brady (2024)
CD5-positive diffuse large B-cell lymphoma is a rare and aggressive entity. Few cases have been described in Latin America. We present the case of a 69-year-old man who develops cervical, iliac, and inguinal lymphadenopathy. Cervical biopsy showed: CD5 positive diffuse large B cell lymphoma. The patient received the R-CHOP regimen for 6 cycles, achieving a complete response. Seven months later, he developed lymph node recurrence receiving the R-ICE regimen with the intention of autologous transplant. The case is described as being a very rare and highly aggressive entity.